THE INFLUENCE OF FREE SHIPPING PROGRAM AND DINING EXPERIENCE ON GEN’Z REPURCHASE INTEREST ON THE SHOPEE FOOD: Pengaruh Program Gratis Ongkos Kirim Dan Dining Experience Terhadap Minat Beli Ulang Gen'z Pada Shopee Food - Briliantine Iswantoro; Afifatus Sholikhah (Universitas Nahdlatul Ulama Sidoarjo, 2024)
In the modern era, there are many digital food delivery services, some of which can deliver almost any type of item, including food and fresh produce. This research aims to further explore whether there is an influence between the free shipping program and dining experience on repurchase intention among Online Food Delivery users. The basis for this objective determination is because Shopee is in line with millennial needs. The method used is a quantitative method by applying purposive sampling based on one's own judgment based on certain criteria or characteristics, it is hoped that it can provide relevant information and answer all research questions. The respondents of this research are Shopeefood service users who have made purchases at Shopeefood services ranging from ages 15 to 23 years. The results of this research are 100 people who used the shopeefood delivery service in this study with the characteristics of age, gender, occupation, order history, type of order. The conclusion from this study was that respondents from gender were 67% women and 33% men. Second, the largest number of vulnerable respondents were aged 21-23 years. Third, most of the respondents were students compared to workers.